Confessions of guilt from torture to Miranda and beyond - Thomas, George C. (George Conner), 1947-; Leo, Richard A., 1963- (Oxford : Oxford University Press, 2012)
George C. Thomas III and Richard A. Leo tell the story of how the law of interrogation has moved from indifference about extreme force to concern over the slightest pressure, and back again. The history of interrogation in the Anglo-American world, they reveal, has been a swinging pendulum rather than a gradual continuum of violence.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Police questioning -- History; Confession (Law); Torture